An Analysis the use of Cohesion and Coherence in Writing Recount Text - Herni Berkat Gulo; Libertina Lase; Ros Ratna Lawolo; Yuslinda Sari Zega (Journal on Education, 2023)
Cohesion and coherence are aspects of writing that aim to improve the quality of writing. However, maintaining cohesion and coherence in a text is a challenge for some students, especially those who learn English as a foreign language (EFL). As a nonverbal communication medium, a text's coherence and cohesiveness are crucial in determining how well readers will understand the message contained in it. This study aims to find out the types of cohesive devices used by the students, and the percentage of cohesive and coherent recount texts of the students. The participants in this study were 20 students of class B in semester 5 of the English education study program. The type of research used is qualitative research. Based on the initial observation of English Department students, this study found that students were able to maintain cohesion and coherence components in their recount texts. The results showed that the students' recount texts reached a good level of application of cohesion and coherence components. This is shown by the students' average score is 94%, which shows that the students utilized cohesion devices to build the coherence of their texts.